The occurrence and origins of some alkylphenols in crude oils - Ioppolo-Armanios, Marisa (Curtin University, 1996)
Analytical procedures have been developed for the quantitative analysis of phenols in crude oils and sedimentary rock pyrolysates and extracts. The procedures involve isolation of the phenolic components of the sedimentary organic matter by extraction with alkaline aqueous methanol, followed by the removal of carboxylic acids using a back extraction step. Co-extracted non-polar components are removed from the alkaline extract by liquid chromatography or by extracting it with hexane. The phenol isolates thus obtained were analysed by capillary GC, GC-MS and GC-FTIR. Recoveries of 70-95% were measured for C(subscript)0-C(subscript)3 alkylphenol compounds using these procedures.Crude oil samples (45) representing a range of locations, ages, depositional environments, maturities, source types, and biodegradation levels have been analysed for their phenol contents. A range of C(subscript)0-C(subscript)5 alkylphenols (approximately 40) were identified in crude oils using co-chromatography on up to three different stationary phases and by comparison of their retention times, mass spectral and infrared spectral properties with reference compounds. Isopropylmethylphenols (six) and sec-butylmethylphenols (nine) were synthesised for use in the identification of these compounds. A range of C(subscript)0-C(subscript)4 alkylphenols (24) were quantified using a dimethyl siloxane column (BP 1 or DB 1) and found to occur at concentrations ranging from 190x10(subscript)3 ng/g down to the limit of detection of 10 ng/g (ppb).The crude oil samples were classified into six groups based on their C(subscript)0-C(subscript)5 alkylphenol compositions. Group 1 crude oils have at least one isomer class in which the relative proportions of the alkylphenol isomers reflect their relative thermodynamic stabilities. The vast majority of samples, however, do not contain relative proportions of phenols which reflect their stabilities, and these differences have been used to group the remaining crude oils. Group 2 crude oils contain predominantly alkylphenols derived from natural product precursors. This group has been further subdivided into Group 2A in which samples have isopropylmethylphenol distributions dominated by carvacrol and thymol; and Group 2B which is comprised of crude oils that contain high relative abundances of methylphenols which can be derived from tocopherols. Group 3 crude oils have C(subscript)2-C(subscript)5 alkylphenol compositions dominated by ortho and para substituted phenols which are proposed to be formed from geosynthetic processes. Group 4 crude oils contain alkylphenol compositions in which the relative abundances of meta substituted compounds in six isomer classes are much greater than those expected from chemical equilibration. Group 5 comprises of samples which are biodegraded and as a consequence contain alkylphenols below the limit of detection. Group 6 crude oils contain very low concentrations of alkylphenols and comprises samples which are derived from source rocks that pre-date the widespread occurrence of land plants or contain negligible land plant input.Some alkylphenols in crude oil are structurally related to natural product precursors and therefore appear to be biomarkers. The monoterpenoid natural products carvacrol and thymol, or its rearrangement product 3-isopropyl-5-methylphenol, which occur in high relative abundances in Group 2A samples are such compounds. Because carvacrol and thymol occur widely in extant conifers and angiosperms, their presence in crude oils derived from source rocks deposited when these plant types were widespread suggests they also originate from these plants. A range of trimethylphenols and tetramethylphenols which occur in high relative abundances in Group 2B samples, are also reaction products obtained from heating alpha-tocopherol with aluminium smectite. This, together with the reported widespread occurrence of tocopherols in plant photosynthetic tissue and in sedimentary rocks, leads to the conclusion that tocopherols are likely precursors to these petroleum methylphenols.The lignin components of terrestrial plants also appear to be important precursors to petroleum alkylphenols. Strong evidence for this is provided by the observation that crude oils derived from source rocks which contain negligible higher plant input contain very low concentrations of kylphenols (Group 6). In order to determine the likelihood of lignins as precursors of petroleum alkylphenols, the phenol contents of coals of lignitic through to bituminous rank were examined. The unbound phenolic components of the lignite samples were analysed by isolating the phenols from their dichloromethane extracts, and the bound phenolic components were analysed by pyrolysis GC-MS. At lignitic rank the unbound methoxyphenols allowed taxonomical classification of the samples and the bound hydroxyphenols bore structural similarities to lignin moieties. The bound C(subscript)0-C(subscript)4 alkylphenol components of lignitic, subbituminous and bituminous coals in a sedimentary sequence were quantitatively analysed by isolating the phenols from their hydrous pyrolysates. In the coals of subbituminous and bituminous rank, the bound alkylphenol components could not easily be related to lignin precursors because molecular transformations of lignins are very severe at these ranks. The increases in the individual concentrations and relative proportions of alkylphenols with methyl and/or isopropyl substituent(s) in the ortho and para positions in the subbituminous coal pyrolysate were attributed to electrophilic methylation and isopropylation reactions occurring to lignin structures in coals during coalification. The dominance of ortho and para substituted methylphenols in coaly Group 3A crude oils which were also observed in the hydrous pyrolysates of coals suggests that the altered lignin structures in coals may be precursors of some of these petroleum methylphenols.Methylation, isopropylation and sec-butylation, are proposed as geosynthetic processes to account for the alkylphenol compositions of crude oils with phenol distributions dominated by ortho and para alkyl-substituted compounds (Group 3). Many crude oils show high relative abundances of ortho and para substituted C(subscript)1-C(subscript)5 alkylphenol isomers and some were also enriched in C(subscript)3-C(subscript)5 alkylphenols compared to kerogen pyrolysates. Because the alkylphenol products obtained from the laboratory alkylation of cresols have distributions which closely resemble those in these crude oils, it is proposed that similar alkylation processes occur in source rocks. Alkylation ratios reflecting the degree of methylation, isopropylation and sec-butylation, which were based on the relative abundance of the dominant alkylation products compared to their likely precursor ortho cresol, indicate that high levels of methylation occurred in crude oils over a wide range of maturities. In contrast, high levels of isopropylation and sec-butylation were observed only in mature samples. Selective dissolution of phenol isomers in crude oils by water contact was discounted as an explanation for the observed phenol distributions based on the relative distribution coefficients of phenols between isooctane and water.The alkylphenol compositions of the remaining crude oils appear to be produced from alteration processes occurring in the subsurface; these include oxidation and biodegradation processes. Oxidation of alkylphenols is proposed to account for the alkylphenol compositions of Group 4 crude oils. Because ortho and para substituted alkylphenols are more susceptible to oxidation than their meta substituted counterparts, the selective removal of these compounds via an oxidation process is suggested as an explanation for the high relative abundances of meta substituted isomers observed in these crude oils. A natural product origin for these compounds appears unlikely due to the lack of known natural products which could give rise to meta substituted alkylphenols with isopropyl substituents, and the diverse range of organisms required to give rise to the meta substituted phenols with n-alkyl substituents observed in Group 4 samples.Crude oils from two Australian basins which have undergone various levels of biodegradation were analysed to assess biodegradation effects on petroleum alkylphenol compositions. Alkylphenols could not be detected in the moderately to severely biodegraded crude oils (Group 5) whereas related non-biodegraded samples contained relatively higher levels of alkylphenols. The very low levels of phenols in the biodegraded samples (< 10 ppb) suggests that phenols are depleted via processes that occur during biodegradation. Because water washing often co-occurs with biodegradation, the very low levels of alkylphenols in these samples may also be due in part to the removal of these polar components via water dissolution.